2006
DOI: 10.1016/j.molcel.2006.11.027
|View full text |Cite
|
Sign up to set email alerts
|

The Checkpoint Clamp Activates Mec1 Kinase during Initiation of the DNA Damage Checkpoint

Abstract: Yeast Mec1/Ddc2 protein kinase, the ortholog of human ATR/ATRIP, plays a central role in the DNA damage checkpoint. The PCNA-like clamp Rad17/Mec3/Ddc1 (the 9-1-1 complex in human) and its loader Rad24-RFC are also essential components of this signal transduction pathway. Here we have studied the role of the clamp in regulating Mec1, and we delineate how the signal generated by DNA lesions is transduced to the Rad53 effector kinase. The checkpoint clamp greatly activates the kinase activity of Mec1, but only i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
196
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(208 citation statements)
references
References 37 publications
10
196
0
2
Order By: Relevance
“…However, the mechanism by which the 9-1-1 complex contributes to this process has remained enigmatic. A recent study shed light on the interplay between the 9-1-1 complex and ATR in S. cerevisiae (Majka et al 2006). Using a reconstituted system of purified proteins, this work showed that the S. cerevisiae 9-1-1 complex (Ddc1, Mec3, and Rad17) directly activated the ATR homolog (Mec3) to phosphorylate multiple substrates, including the kinase Rad53.…”
Section: Resultsmentioning
confidence: 99%
“…However, the mechanism by which the 9-1-1 complex contributes to this process has remained enigmatic. A recent study shed light on the interplay between the 9-1-1 complex and ATR in S. cerevisiae (Majka et al 2006). Using a reconstituted system of purified proteins, this work showed that the S. cerevisiae 9-1-1 complex (Ddc1, Mec3, and Rad17) directly activated the ATR homolog (Mec3) to phosphorylate multiple substrates, including the kinase Rad53.…”
Section: Resultsmentioning
confidence: 99%
“…A recent publication demonstrated that the loading of the 9-1-1 clamp onto DNA can stimulate the phosphorylation of Mec1 substrates in vitro (12). Because Mec1-Ddc2 also associates with DNA (28), the loaded clamp may serve as a scaffold for the recruitment of other Mec1 substrates.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that Ddc1 and/or a Ddc1-interacting protein may function as a direct activator of Mec1. In fact, Ddc1 purified from yeast has been shown to modestly stimulate the kinase activity of Mec1 in vitro under low-salt conditions (12).…”
mentioning
confidence: 99%
“…It is interesting to note that most of them are nuclear proteins involved in DNA replication and repair, DNA damage checkpoint, and RNA metabolism and transcription. Among them, Rpa1 and Mec3 were reported to be directly phosphorylated by Mec1 and/or Tel1 (24,33) and Rad9 was known to undergo a Mec1/Tel1-dependent phosphorylation (34,35). The other targets are previously undescribed findings.…”
Section: Quantitative Proteomic Approach For Comparative Analysis Of mentioning
confidence: 99%